Use of End-to-End Tool for the Analysis of the Digital Governance of Ports - Nicoletta González-Cancelas; Alberto Camarero Orive; Alberto Rivas Vilarchao; Javier Vaca-Cabrero (Logistics)
Background: Digital governance currently presents challenges in the context of ports, where efficiency and transparency are key elements for the success of operations. In ports, the effective adoption of digital governance can have a significant impact on optimizing operational processes and improving coordination between port authorities, logistics operators and customs. Method: In this context, the article proposes the use of an End-to-End Tool to analyze and evaluate digital governance in ports. This tool makes it possible to collect data from various sources, carry out a thorough analysis of the processes involved, and evaluate the satisfaction of end users. In addition, it provides an intuitive and easy-to-use interface to visualize results and make evidence-based decisions. The outcomes revealed areas of improvement in operational processes, identified bottlenecks, and presented proposals to optimize port efficiency. Results: The port currently exhibiting the best digital governance is Valencia, followed by Piraeus, Barcelona, and Algeciras, with very comparable management, and finally, Genoa. Conclusions: Efficient public–private collaboration in digital governance boosts port competitiveness. Regulatory frameworks for data security are crucial, and digital governance emerges as vital for global success.